Eksistensi Undang-Undang Cipta Kerja Pasca Putusan Mahkamah Konstitusi Nomor 91/PPU-XVIII/2020 - Aditya Pria Setyady; Chrisdianto Eko Purnomo; M. Saleh (Jurnal Diskresi, 2024)
This study aims to find out and understand the existence of the Job Creation Law after the Constitutional Court Decision Number 91/PPU-XVIII/2020, and the legal meaning of the Job Creation Law after the Constitutional Court Decision Number 91/PPU-XVIII/2020 in terms of legal certainty . The research was carried out using normative research methods, using regulatory, conceptualization and case approaches. The research results show that the existence of the Job Creation Law has an impact on the status of Constitutional Court Decision No. 91/PPU-XVIII/2020 between existence and absence. It is said to exist because it is used as a juridical basis in the Job Creation Law, but substantively the decision of the Job Creation Constitutional Court, especially the constitutional order to substantively improve the Job Creation Law by involving meaningful community participation, is not implemented. The government (in this case the President) actually uses the Job Creation Law instrument which substantively denies the Job Creation Constitutional Court's decision. The legal implications of the Job Creation Law after the Job Creation Constitutional Court's decision have an impact on the law regarding the formation of statutory regulations, because after the Job Creation Constitutional Court's Decision a new concept was accommodated in the form of an omnibus law which had never previously been accommodated by Indonesia. Apart from that, the existence of non-compliance with the Job Creation Law with the Constitutional Decision of the Job Creation Court has the potential to give rise to the phenomenon of constitutional disobedience. Therefore, in the future, it is necessary to formulate the form and type of sanctions for Constitutional Court Decisions and also orientate the Constitutional Court to be able to carry out reviews of laws or laws that conflict with Constitutional Court Decisions. Keywords:Legal Implications: Constitutional Court Decision, Job Creation Law.